Multicell adaptive power allocation scheme based on game theory in OFDMA systems - ZHANG Tian-kui; ZENG Zhi-min; ZHANG Ying-ying (Tongxin xuebao)
A multicell power coordinated allocation scheme was proposed for downlink orthogonal frequency division multiple access （OFDMA） cellular systems. Transmit power levels of co-subchannels were coordinated among inter-cell, consequently inter-cell interference was mitigated and channel capacity was increased. Game theory was employed in the multicell power allocation. A multicell non-cooperative power allocation game framework was presented via pricing. The existence and uniqueness of Nash equilibrium of this game framework was analyzed, and a distributed algorithm for this game was proposed. The performance of the proposed scheme is verified by simulation in the single cell and multiple cell scenario respectively, as well as the influence of pricing factor on system performance. Simulation results show that the multicell power coordinated allocation scheme proposed will improve radio resource efficiency, increase throughput of the system, and reduce the average transmit power.